On method acting - Dwight, Edward (Ivy Books, 2013)
Practiced by such actors of stature as Marlon Brando, Robert De Niro, Julie Harris, Dustin Hoffman, and Ellen Burstyn (not to mention the late James Dean) the Method offers a practical application of the renowned Stanislavsky technique. On Method Acting demystifies the "mysteries" of Method acting -- breaking down the various steps into clear and simple terms, including chapters on: Sense Memory -- the most vital component of Method acting Improvisation -- without it, the most integral part of the Method is lost Animal Exercises -- just one way to combat the mental blocks that prevent actors from grasping a character Creating The Outer Character -- so actors can give the freshness of originality to a role while at the same time living the life of the character On Method Acting is also an indispensable volume for directors, designers, lighting technicians, and anyone in the dramatic arts interested in creating a believable and realistic effect in their productions.